THE STUDY ON TEACHERS' ABILITY IN USING ITEM ANALYSIS ON READING TEST AT ELEVENTH GRADE SMA MUHAMMADIYAH TEMBILAHAN - Aniswati; Ardian, Edi; Maizarah (Program Studi Pendidikan Bahasa Inggris, 2023)
This study aims to describe the Items Analysis of the Reading Test Assessment Questions in Class IX SMA Muhammadiyah. This research is quantitative descriptive. Subject in This research is class IX students, totaling 16 students. Data collection techniques using the test method. The data were analyzed using the Excel program. The results of this study indicate that; There are 20 multiple choice questions the results are as follows: (1) In terms category of the level of difficulty, 11 items are found in the Hard category, 6 items in the medium category, 3 items in the easy category, (2) In terms category the category Discrimination power, there are 0 items that have very poor discriminatory power, 11 items have poor discriminatory power, 8 items have satisfactory discriminatory power, 1 item has good distinguishing power, and 0 items have good power excellent differentiator (3) In terms of the effectiveness of the distractor who chooses option Atotal of 17 items were accepted and 3 items were rejected, who chose option B as many as 19 items were accepted and 1 item was rejected, who chose option C as many as 19 items were accepted and 1 item was rejected, who chose option D as many as 18 items were accepted and 2 items were rejected, and those who chose option E were 17 items accepted and 3 items were rejected.